'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

Klopstocks lyrisches Spätwerk. Perspektivwechsel und Blickerweiterungen - Elit, Stefan („Wer wird nicht einen Klopstock loben?“ Friedrich Gottlieb Klopstocks poetische Innovationen und ihre produktive Rezeption)

Lines in the Sand - Langer, Svenja

Vincent Mosco’s Critical-Humanist Political Economy of Communication - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Virtuelle Ensembles. Große Musik in kleinen Kacheln mit der Acapella-App - Gosmann, Phillip (Musik und Unterricht)

Imagining and Governing Artificial Intelligence – the Ordoliberal Way: An Analysis of the National Strategy ‘AI Made in Germany’ - Hälterlein, Jens (AI & Society)

Team-Teaching und Kompetenzen von Kindern im inklusiven naturwissenschaftlichen Sachunterricht. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven". - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effekte eines universitären Kooperationstrainings auf inklusionsbezogene Selbstkonzepte von Lehramtsstudierenden. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven". - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effekte eines universitären Lehrerkooperationstrainings auf die inklusionsbezogenen Selbstkonzepte angehender Lehrkräfte. Vortrag auf der 11. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung verstehen – Partizipation erreichen – Transfer gestalten“. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effects of a collaborative teacher education on pre-service teachers’ inclusion-related self-concept. Oral Paper Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effects of University Teacher Collaboration Training on the Inclusion-Related Self-Concepts of Prospective Teachers. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Reflexion im Dialog. Ein Modell für eine Kinder, Eltern, Teams und Schule stärkende Bildungsdokumentation. - Büker, Petra; Höke, Julia (Grundschule aktuell)

Kinderstärkende Pädagogik in der Schule im Kontext aktueller Herausforderungen. Kennzeichen, Anfragen und mögliche Blinde Flecke. Keynote an der Tagung: Die Kunst der Partizipation. PH Zürich. - Büker, Petra

Ich darf auch „Nein“ sagen: Das Kinderrecht auf informierte Einwilligung und dessen Implikationen. Beitrag im Rahmen des Symposiums „Partizipation an, mit und über Forschung? Dilemmata und forschungsethische Reflexionen im Prozess des Forschens mit Kindern. Symposium an der Tagung: Die Kunst der Partizipation. PH Zürich. - Büker, Petra; Deckert-Peaceman, Heike; Hüpping, Birgit; Zala-Mezö, Enikö

A Healing Media System of Care - Cancer Diaries and Social Media - de Gruisbourne, Birte; Schulz, Christian (Inquiring healing across screen cultures: Recuperating narratives, mediums, and creativities)

HenDi-Data (data package) v4.0.0 - Ried, Dennis; Minetti, Elena; Capelle, Irmlind; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-ODD v4.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v4.0.0 - Ried, Dennis

Critical Perspectives on Digital Capitalism: Theories and Praxis (tripleC: Communication, Capitalism & Critique)

Critical Theory Foundations of Digital Capitalism: A Critical Political Economy Perspective - Fuchs, Christian (tripleC: Communication, Capitalism & Critique.)

Critical Perspectives on Digital Capitalism: Theories and Praxis. Introduction to the Special Issue - Fuchs, Christian; Arslan, Sevda Can; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Schulleitungen als Promotoren. Unterstützung digitalisierungsbezogener Schulentwicklungsprozesse durch Schulleitungen und deren Wahrnehmung durch Lehrpersonen. - Gerick, Julia; Kieseler, Janine; Herrmann, Daniel; Eickelmann, Birgit (MedienPädagogik (Occasional Papers))

Zwischen Herrschaft und Utopie . Eine theologische Reflexion über die ambivalente Mensch-Tier-Beziehung - Herdramm, Henrike (Laudato)
Keywords: Tiertheologie; Tierethik; Psalm 104; Mensch-Tier-Beziehung

Modellierungen außerinstitutioneller Aneignungsprozesse digital-materieller Interfaces und (musik-)pädagogische Anschlüsse - Neuhausen, Timo; Ahlers, Michael (Musik – Digitalisierung – Bildung)

Singen auf TikTok und Co. Sind Gesangspraktiken in (post)digitaler Kultur (k)ein Thema für die Musikpädagogik? - Godau, Marc (Stimme, Medien, Umwelt. Kinder- und Jugendstimme)

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Liveness-Norm in der Musikpädagogik – warum die Orientierung an Live-Musik kulturelle Vielfalt und Digitalisierung verhindert - Godau, Marc; Gosmann, Phillip (Seminar)

Street Signs, New York (2018). - Autsch, Sabiene (Festschrift für Thomas Krettenauer)

Pop-Ikonen. Transformationen des Heiligen in der deutschen Pop(musik)kultur. - Jacke, Christoph; Schroeter-Wittke, Harald ((Un)verfügbar. Kulturen des Heiligen.)

Homiletischer "freejazz". Des Gerechten Gebet vermag viel. Eine Partytour - Schroeter-Wittke, Harald; Scheidegger, Martin (Pastoraltheoogie)

Quasimodogeniti (07.04.2024) Joh 20,19-20(21-23)24-29: Vom Safe Space zum Escape Room: Der gläubige Thomas - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Seven Psalms. Paul Simons theologische Kammermusik - Schroeter-Wittke, Harald (Praktische Theologie)

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern [i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi [ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann).
Keywords: Inklusion; Kooperation; Eltern; Sekundarstufe 1; Evaluation; Integration; Schulentwicklung; Elternkooperation

Religion und Freiheit - Süßmann, Johannes

Weihnachts-Werbespots als moderne Krippenspiele

Von Transzendenz zum Transhumanismus. Deutungskulturen von (Un-)Heilsgeschichte im 19. und 20. Jahrhundert

Kraft, Kerstin und Regina Lösel: Forscherinnen und Kleidung in Bewegung. - Kraft, Kerstin

Mathematikleistungen von Grundschulkindern im Zusammenhang mit dem von ihnen wahrgenommenen Feedback und ihrer Motivation im Mathematikunterricht. Vortrag auf der 11. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung verstehen – Partizipation erreichen – Transfer gestalten“ - Finke, Nils; Hellmich, Frank

An eye-tracking study on pre-service teachers' professional vision in class. Poster Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Görel, Gamze; Finke, Pauline; Hellmich, Frank

A mixed‐methods study of the quality of parental support during adolescents' information‐related Internet use as a co‐construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)
Abstract Introduction In Europe, most Internet searches for school‐related tasks are situated at home, where parents can support adolescents. Although the frequency (quantity) of parental support has already been analyzed, a research gap exists concerning the quality of parental support in adolescents' information‐related Internet use. The quality of parental support in the field of homework involvement is known to be a predictor of adolescents' learning motivation and academic achievement, often discussed with regard to self‐determination theory (SDT) in terms of autonomy support, structure, emotional support, and control. These categories were adapted in this study to analyze parents' support in adolescents' Internet searching activities. Methods Using a mixed‐methods approach, we combined quantitative questionnaires and qualitative observations to analyze joint information‐related Internet uses. Therefore, 243 parent–adolescent dyads were surveyed and six parent–adolescent dyads were observed by videography in 2019/2020 in Germany. The adolescents were 11 years old, on average. Results The parents rated all qualities higher than the adolescents. Emotional support was rated highest by both groups, whereas structure was rated lowest. Adolescents' and parents' view on parental support differ. The qualitative study revealed parents' often interfering behavior, whereas emotional support was low. Further, the active role of adolescents was highlighted in both quantitative and qualitative data. Conclusions By combining quantitative and qualitative approaches, we demonstrated a fruitful application of SDT in analyzing the quality of parental support during adolescents' Internet searches at home and shed light on the co‐construction of joint Internet searches.
Keywords: Psychiatry and Mental health; Developmental and Educational Psychology; Social Psychology; Pediatrics; Perinatology and Child Health

Zermelo - Peckhaus, Volker (Neue Deutsche Biographie, Bd. 28: Wettstein - Zwoch)

Leibniz, Gottfried Wilhelm, General Inquiries on the Analysis of Notions and Truths, edited with an English translation by Massimo Mugnai, Oxford University Press: Oxford 2021 (BSHP New Texts in the History of Philosophy) - Peckhaus, Volker (Mathematical Reviews, MR457231)

“It’s like I got a new pair of glasses”: Reflections on sense of self, home, and belonging among transnational students in short-term study abroad programs - Müller, Mareike (Study Abroad Research in Second Language Acquisition and International Education)
This study focuses on a specific group of sojourners that has thus far remained rather unexplored in the context of study-abroad research, namely, students with extensive prior experiences of living in, traveling to, and/or familial ties with target-language mediated communities. To this end, this study examines data obtained through episodic interviews with three American students, who grew up in close contact with German-speaking communities and studied abroad in Austria for four weeks. By means of thematic analysis, the pre-study abroad sojourn motives and reflections on sense of self, home, and belonging are contrasted with these students’ immediate and delayed post-study abroad accounts. The results shed light on both the challenges young adults grapple with due to their international biographies and the transformative effects students attribute to their short-term sojourns with regard to redefining who they are and what meaning different places of home and heritage have within their individual trajectories.

Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Die Sporthalle – Ein Raum zum Sprachenlernen? Zwischen der Forderung nach Integration durch Sport und Sprache(n) als Schlüssel zur Integration - Treder, Alexandra (Transdisziplinäre Räume in den Kultrwissenschaften)

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Nur Provokation oder doch politisches Statement? Der Spot "The Journey" von 84 Lumber aus dem Jahr 2017 - Janus, Richard; Müller, Emma (Weihnachts-Werbespots als moderne Krippenspiele)

Werbung, Krippenspiele und Religion. Einleitende Bemerkungen - Janus, Richard (Weihnachts-Werbespots als moderne Krippenspiele)

Soziale Grenzen und Grenzbearbeitungen. Ein Zugang zur sozialwissenschaftlichen Bildungsforschung - Haker, Christoph; Otterspeer, Lukas (Bildungsforschung: Erziehungswissenschaftliche Perspektiven)
Der Beitrag führt in die von uns verfolgte Forschungsperspektive der sozialen Grenzen und Grenzbearbeitungen ein und bringt diese mit den Begriffen Bildung und Bildungsforschung zusammen. Unsere Theoretisierung beginnt mit einem sozialtheoretisch unterbestimmten Verständnis sozialer Grenzen und Grenzbearbeitungen. Dieses erhebt einerseits den Anspruch, nah an Alltagserfahrungen mit sozialen Grenzen und Grenzbearbeitungen zu sein. Andererseits ermöglicht es den Einstieg in ganz unterschiedliche Sozialtheorien und damit eine multiperspektivische Forschungspraxis. Dieses Potential plausibilisieren wir am Beispiel von Analysen zu Fragestellungen der Wissenschafts- und Rechtsextremismusforschung, die wir selbst durchgeführt haben. Für Bildung und Bildungsforschung sind in diesem Zusammenhang der Blick auf Bildungsprozesse, Bildungsinstitutionen und die Konzeption von Forschung als eine selbstreflexive Bildungspraxis relevant.

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

The Ability and Intention of Not Paying Taxes in History. Some Introductory Observations - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea (Histories of Tax Evasion, Avoidance and Resistance)
Jean Bodin's list on how the absolutist monarchical state could raise its revenue ranked taxation only in seventh place. From a modern legal perspective, taxes are compulsory transfers of resources that households and enterprises pay to one or several government bodies without receiving an individual, specific benefit in return. Historians have dealt with not paying taxes in various contexts, such as analysing tax resistance and tax resistance movements in history. Tax law is best understood as an outcome of long-term, often conflictual, negotiations and as an expression of specific political mentalities and ideologies. As a consequence, tax law and sometimes even the tax juridical system have a strongly politicised character. Loopholes in tax legislation that enable or facilitate avoidance or evasion can thus be regarded as a result of the interest-driven politics of parliamentary majorities, as the success of concerted lobby pressure.

How to Create a Taxpaying Spirit. A Transnational Examination of an US American and a Western German Tax Education Film in and after World War II - Schönhärl, Korinna (Histories of Tax Evasion, Avoidance and Resistance)
As a case study, this chapter examines two tax education films that were produced 11 years apart in the USA and Western Germany during and after World War II: “The New Spirit” and “Putzke wants to know”. In contrast to America's most popular cartoon character 11 years earlier, Erwin Putzke is in a terrible mood at the beginning of the short film “Putzke wants to know”. The family father and electrician with a workshop of his own is annoyed and upset by the duty of filling in his tax return, grumbling at his wife and daughter and even at their budgie. The film's tax morale message is conveyed to its audience against the backdrop of a sober post-war reality characterised by allied occupation and the Allies' say in West German tax policies during a period of laborious economic build-up after a lost war.

Bibliotheken des Hellwegraums als Orte frühneuzeitlichen Kulturtransfers. Aufriß und Forschungsprogramm - Süßmann, Johannes (Bücher in Westfalen – Westfalen und ihre Bücher. Festschrift für Hermann-Josef Schmalor zum 70. Geburtstag)

Antonia Villinger: Dramen der Schwangerschaft. Friedrich Hebbels „Judith“, „Maria Magdalena“ und „Genoveva“. Baden-Baden: Ergon 2021 - Famula, Marta (Jahrbuch Forum Vormärz Forschung 2022. [in Vorbereitung])

In der freiheit musicirt: Musikpraxis und -erziehung in den Taschenkalendern Kaspars von Fürstenberg - Lauert, Markus (Musiklandschaften zwischen Pader und Rhein. Verflechtung und Pluralisierung entlang des Hellwegs)

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“ - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Literaturen vom 19. bis zum 21. Jahrhundert (thematische, ästhetische, mediale Transformationen hin zu einer technologisch aufgerüsteten Weltkommunikation) - Öhlschläger, Claudia (Grundthemen der Literaturwissenschaft: Weltliteratur.)

Rezension: Chiara Conterno / Astrid Dröse: Deutsch-italienischer Kulturtransfer im 18. Jahrhundert. Konstellationen, Medien, Kontexte - Süwolto, Leonie (DAJ)

Effekte eines Interventionsprogramms zur Förderung der sozialen Partizipation auf die Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“. - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Tschirk, Wolfgang. "Vom Universum des Denkens. Eine Geistesgeschichte der Logik". Springer: Berlin 2022, xvii, 117 S. - Peckhaus , Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Politisch-humanistische Positionen in Reisenarrativen über Frankreich der 1920er und 1930er Jahre:„La lumière“ – Joseph Roths poetischer und medienreflexiver Humanismus - Öhlschläger, Claudia (Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa.)

Schule und Schulträger im Dialog: Gelingensbedingungen von Runden Tischen zur gemeinsamen Gestaltung des Digitalisierungsprozesses - Hagemann, L.; Herzig, Bardo; Möller-Glesemann, B. (Schulwelt NRW)

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Immaterielles Kulturerbe in Nordrhein-Westfalen. Zur Bedeutung kultureller Ausdrucksformen - Harnack, Maria (Immaterielles Kulturerbe und regionale Identität – Schützenwesen in Deutschland)

Deutscher Werkbund, Bauhaus, Hochschule für Gestaltung Ulm - Seng, Eva- Maria

Zu »wahrer Glückseligkeit« anleiten. WWU-Gründervater Franz von Fürstenberg wollte vor allem den Fortbestand des Landes sichern – ein Gastbeitrag - Süßmann, Johannes (wissen/leben. Die Zeitung der WWU Münster)

Sprachliche Bildung - Topalović, Elvira; Settinieri, Julia

Improving students’ attitudes towards peers with special needs: Results from an intervention study. Symposium "Chances and challenges in diverse classrooms" (Sepideh Hassani & Marwin Felix Loeper). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Prerequisites for primary school teachers’ practices in the inclusive classroom. Symposium "Applying the Theory of Planned Behavior in Inclusive Education« (Olli-Pekka Malinen). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)

Digital Ethics. Media, Communication and Society Volume Five - Fuchs, Christian

Der digitale Kapitalismus. Arbeit, Entfremdung und Ideologie im Informationszeitalter - Fuchs, Christian

Adorno and the Media in Digital Capitalism - Fuchs, Christian (Adorno und die Medien: Kritik, Relevanz, Ethik)

Digitalität, Mediatisierung und Bildung - Megatrends aus medienpädagogischer Perspektive - Herzig, Bardo (Bildung und Digitalität. Analysen - Diskurse - Perspektiven)

Modellbildung und Modellnutzung in der Allgemeinen Didaktik - Herzig, Bardo (Pädagogische Rundschau. Sackgasse oder Meilenstein? Zur Sinnhaftigkeit von Modellbildungen in der Erziehungswissenschaft)

Kinderstärkende Pädagogik in der Grundschule im Kontext (post-)pandemischer Herausforderungen. Kennzeichen, Kritische Anfragen und Blinde Flecke. Vortrag an der Tagung: Was Resilienz stärkt. Chancen und Risiken eines immer populärer werdenden Konzepts. Pädagogische Hochschule Heidelberg. - Büker, Petra

KrafT: Bildungsdokumentation in der inklusiven Schule partizipativ gestalten. 9. Paderborner Grundschultag zum Thema: „Demokratie Lernen von Anfang an“. Online - Büker, Petra; Herding, Jana; Drexler, Leonie

Near-Term Effects of Short-Term Study Abroad: A Longitudinal Examination of Learner Perceptions - Müller, Mareike (Frontiers: The Interdisciplinary Journal of Study Abroad)
A relatively small body of research has been conducted on the near- and long-term effects of study abroad (SA) to date. This existing research suggests that SA effects on language skills tend to be volatile, while the impact on various aspects of learners’ personal, academic, and professional development may be longer-lasting. Yet, learner perspectives on the dynamics and durability of such effects, in particular in the context of short-term SA programs, remain largely unexplored. This study hence investigates the near-term impact of short-term SA programs as experienced by students within the first months and years following their sojourns. A qualitative case-study design is employed to examine the accounts of four American students of German, who studied abroad in Austria for four weeks and were interviewed repeatedly over a period of up to 40 months after their sojourns. The results suggest that, from the students’ perspective, many effects deteriorate in the near term, although the overall sojourn experience still appears influential. Abstract in German Nur wenige Forschungsvorhaben haben sich bislang den mittel- bis langfristigen Auswirkungen studentischer Auslandsaufenthalte gewidmet; die bisherige Datenlage deutet jedoch darauf hin, dass die Auswirkungen auf sprachliche Kompetenzen eher unbeständig sind, wohingegen die persönliche, studiums- und berufsbezogene Entwicklung der Lernenden länger von einem Auslandsaufenthalt beeinflusst wird. Die Dynamik und Beständigkeit derartiger Auswirkungen wurden jedoch kaum mit Blick auf kurze Auslandsaufenthalte (≤ acht Wochen) sowie aus der Perspektive der Studierenden erforscht, was die vorliegende Studie insbesondere hinsichtlich mittelfristiger Effekte fokussiert. Mittels eines qualitativen Fallstudiendesigns werden die Interviewdaten vier amerikanischer Deutschlernender untersucht, die sich vier Wochen in Österreich aufhielten und in einem Zeitraum von bis zu 40 Monaten nach ihrem Aufenthalt wiederholt befragt wurden. Die Ergebnisse zeigen, dass viele Auswirkungen eines solchen Aufenthalts aus studentischer Perspektive mittelfristig verblassen, auch wenn der Auslandsaufenthalt im Gesamten weiterhin als einflussreiche Erfahrung wahrgenommen wird.

Examining the Measurement Invariance and Convergent Validity of the SSIS-SELb-Student in Austria and Germany. 44th Annual Conference of the International School Psychology Association (ISPA) 2023. - Anthony, Christopher J.; Yost, M; Howe, A; Schwab, Susanne; Hassani, Sepideh; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Writing as Narrative Resource in Therapeutic Settings: Diaries, Sketches, Notes - Mildorf, Jarmila; Ketteler, Daniel (Narrative and Mental Health Today: Reimagining Theory and Practice)

Narrative and Mental Health: Reimagining Theory and Practice

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

Universities and Academic Labour in Times of Precarisation and Digitalisation - Allmer, Thomas

Bootstrapping the Open Science culture: The fellowship approach - Heck, Tamara; Steinhardt, Isabel; Rahal, Rima-Maria; Schubotz, Moritz; Scholl, Dominik; Behrens, Sarah (Research Ideas and Outcomes)
Keywords: Open Science

Förderung der sozialen Partizipation von Kindern im inklusiven Unterricht. Workshop auf dem 9. Paderborner Grundschultag. Thema: „Demokratie von Anfang an! Demokratie in der Grundschule erfahren, mitgestalten und reflektieren“ - Görel, Gamze; Hellmich, Frank; Löper, Marwin Felix

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Narrative Experiments with Medical Categorization and Normalization in B. S. Johnson's House Mother Normal - Strauß, Sara (Narrative and Mental Health)

Please Mind the Gap. Reconfiguring Solidarity through Space in Michael Nicoll Yahgulanaas' Haida Manga Art. - Jende, Yvonne Kristin (Solidarités. Réseaux – Convivialités – Confrontations/ Solidarities. Networks – Convivialities – Confrontations, 44. Annual Conference of the Association for Canadian Studies in German-Speaking Countries)

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Studien zu Schulleistungen und ihre Aufbereitung - Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Sonderpädagogik; Bildung; Bildungsstudien; Integration

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Learning Computational Thinking in Secondary School (Year 8) in Germany in International Comparison: Results from ICILS 2018 - Labusch, Amelie; Eickelmann, Birgit (Teaching coding in K-12 schools: Research and application)

Die inhaltliche Ausgestaltung schulischer Medienkonzepte als Gelingensbedingung digitalisierungsbezogener Schulentwicklungsprozesse - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (Professionalisierung für digitale Bildung im Grundschulalter - Ergebnisse des Forschungsprojekts P3DiG)

Abschlussbericht zum Forschungsprojekt ‚Gelingensbedingungen und Transfer von erfolgreichen Digitalisierungsprozessen an Schulen in Nordrhein-Westfalen (GuTe DigiSchulen NRW) - Gerick, J.; Eickelmann, Birgit; Panten, B.; Rothärmel, A.; Rau, M.; Gottschalk, T.